CONCEPT OF CONTEMPORARY CONSTITUTIONALISM - Vaičaitis, Vaidotas A. (Teisė, 2017)
This article analyses concept of constitutionalism through three paradigms: i) philosophical constitutionalism as study of different concepts of constitution, ii) so called value constitutionalism, encompassing three main constitutional values (rule of law, democracy and human rights) and iii) interpretative (methodological) constitutionalism as theory on interpretation of constitution. Each one of these three paradigms of constitution may be separate theory of constitution. Such concept is completely new theory on constitutionalism not only in Lithuanian, but also in comparative constitutional law.